Somewhere towards the end : a memoir - Athill, Diana frey50 (New York : W. W. Norton, 2009)
An esteemed memoirist and one of the great editors in British publishing examines aging with the grace of Elegy for Iris and the wry irreverence of I Feel Bad About My Neck.
Originally published in Great Britain by Granta Publications, 2008.
Keywords: Athill, Diana; Old age; Aging; Editors -- Great Britain; Women editors -- Great Britain; Authors, English -- 20th century; Women authors, English -- 20th century; Biography - Memoir